Medical Guide System - Aththanayaka H. A. M. U. I; Senarathne S. M. A. D; Udayantha Yapa Y. M. S; Lakpriya K. H. A. V; D. I. De Silva; S. M. D. T. H. Dias (International Journal of Engineering and Management Research, 2022)
Currently, getting access to emergency services and consumer health services requires calling a knowledgeable person on the regular phone or using different self-care techniques for illnesses without consulting a doctor. We are improving and expanding new channels of personal communication to facilitate interaction between emergency users and the emergency service system. Given the widespread use of smart devices in our society, we are developing a web application called "Quick Health" for emergency management, with the main feature of answering a question asked by another party or evaluating a given answer, as well as posting a problem and exchanging ideas with others. Our goal is to define a platform that is totally usable by everyone, regardless of their technological or linguistic proficiency. This paper's main goal is to clarify how to adapt traditional applications to modern web applications by taking into account not only web technologies but also social networking behavior. Keywords - Healthcare Emergency System: Medical Guidance; User Interaction; Web Applications